Novel submucosal lifting gel for performing endoscopic mucosal resection after precutting in large gastric lesions: An animal feasibility study - Yunho Jung; Chang-Il Kwon; Il-Kwun Chung; Gwangil Kim; Kwang Hyun Ko; Sung Pyo Hong; Seok Jeong; Don Haeng Lee (Society of Gastrointestinal Intervention, 2020)
Background : The submucosal lifting gel (Cook Medical Inc., Winston-Salem, NC, USA) is a novel injectate for submucosal lifting of gastrointestinal lesions. The aim of this study was to evaluate the efficacy of the novel submucosal lifting gel for performing endoscopic mucosal resection after precutting (EMR-P) in large gastric lesions. Methods : A total of 31 artificial lesions were created on body of stomach by electrocautery marking with endoscopic ruler in five live micro-pigs. Three different groups were randomly assigned by the size of artificial lesion such as 3 cm (group 1, 11 cases), 3.5 cm (group 2, 10 cases), and 4 cm (group 3, 10 cases) in diameter. Then EMR-P was performed after injection the lifting gel sufficient unto submucosal layer. Independent observer recorded circumferential resection time, submucosal injection time, injection amount, total procedure time, en bloc and perforation rate. Results : The mean circumferential resection time was significantly longer in the group 3 in comparison with group 1 and 2 (6.7 ± 1.7 min vs 4.2 ± 1.4 min, P < 0.001 and 4.7 ± 1.5 min, P = 0.004). The mean total procedure time and amount of injection were significant difference between three groups (9.6 ± 2.2 min vs 12.9 ± 2.6 min vs 17.4 ± 2.2 min, P < 0.01) (5.2 ± 1.1 mL vs 6.9 ± 1.4 mL vs 9.3 ± 3.0 mL, P = 0.02). The en bloc rate of each group was 90.9% (10/11), 60.0% (6/10), and 50.0% (5/10) in the group 1, 2, and 3 respectively. There was a perforation during circumferential cutting in group 2. Conclusion : In a porcine model, a new submucosal lifting gel seems to improve the en bloc rate for performing EMR-P in large gastric lesions, especially 3 cm in diameter.